2016
DOI: 10.1155/2016/6180487
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of Stem Cells in Bone Tissue Engineering: A Review

Abstract: Mesenchymal stem cells (MSCs) have been the subject of many studies in recent years, ranging from basic science that looks into MSCs properties to studies that aim for developing bioengineered tissues and organs. Adult bone marrow-derived mesenchymal stem cells (BM-MSCs) have been the focus of most studies due to the inherent potential of these cells to differentiate into various cell types. Although, the discovery of induced pluripotent stem cells (iPSCs) represents a paradigm shift in our understanding of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
135
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 107 publications
(134 reference statements)
0
135
0
1
Order By: Relevance
“…Bone tissue engineering techniques with or without ASCs have been studied actively during past decades 26, 27, 28. ASCs are multipotent cells that are recognized as potentially beneficial in wide variety of medical therapies in reconstructive surgery 27, 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone tissue engineering techniques with or without ASCs have been studied actively during past decades 26, 27, 28. ASCs are multipotent cells that are recognized as potentially beneficial in wide variety of medical therapies in reconstructive surgery 27, 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs are multipotent cells that are recognized as potentially beneficial in wide variety of medical therapies in reconstructive surgery 27, 28, 29, 30. The potential of these cells has evoked great enthusiasm and high expectations in both scientific and commercial circles.…”
Section: Discussionmentioning
confidence: 99%
“…The scaffold design for bone tissue engineering involves many parameters that directly affect adhesion, proliferation, and osteogenic differentiation of the seeded MSCs. 35 It has been shown that the nanoscale topographical features, mechanical properties and micro-/macroscale gradient structures, in addition to the biological domains, are the most important elements in successful bone regeneration. 35,36 Moreover, nanoscale particles, like HA, in the scaffold structure can significantly modulate the behavior of the seeded cells, including cell adhesion, differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…35 It has been shown that the nanoscale topographical features, mechanical properties and micro-/macroscale gradient structures, in addition to the biological domains, are the most important elements in successful bone regeneration. 35,36 Moreover, nanoscale particles, like HA, in the scaffold structure can significantly modulate the behavior of the seeded cells, including cell adhesion, differentiation and proliferation. 37 Thereby, bone formation from the seeded allogeneic MSCs, as well as the absence of the host cells, may be determined by the scaffold structure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Bone has a remarkable regenerative potential -fracture healing is a complex process that follows specific regenerative patterns involving several molecular, genetic, biochemical and cellular mechanisms. When the size of the lost bone is greater than the healing capacity of osteogenic tissues there is a need of bone implants.…”
mentioning
confidence: 99%